ESOPHAGEAL STENTING FOR MALIGNANT STENOSIS (three-year outcomes) - A. A. Avanesyan (Вестник хирургии имени И.И. Грекова, 2020)
OBJECTIVE of the study was to analyze the main problems and try to find the ways to improve the esophageal stenting for malignant stenosis with regard to our experience.METHODS AND MATERIALS. Palliative esophageal stenting for malignant dysphagia realized in 103 patients with observing all the patients till the fatal outcome.RESULTS. Early complications were observed in 9 patients (8.7 %) among which were: perforation of esophagus – 1 (0.97 %), minor bleeding – 2 (1.9 %), stent migration – 6 (5.8 %). Elimination of dysphagia as an immediate clinical effect was achieved in all of 103 patients (100 %) among all of early complications included. Delayed sequelae were found in 40 patients (38.8 %) among which were recurrent dysphagia because of tissue in-/overgrowth – 27 (26.2 %), stent migration – 2 (1.9 %), different kinds of esophageal fistulae – 5 (4.9 %), major bleeding – 6 (5.8 %). The most severe life-threatening complications developed at 109 days after stent placement. The mean survival rate was 131 days (from 12 till 546 days).CONCLUSION. Immediate clinical effect of stenting was achieved in 100 % of cases and delayed clinical effect was in 73.8 % of patients. Chemoradiotherapy conduces to increase the mean survival rate and, at the same time, to increase the most severe delayed life-threatening complications after esophageal stenting